Deep ALMA photometry of distant X-ray AGN: improvements in star formation rate constraints, and AGN identification. Issue 3 (7th May 2018) - Stanley, F; Harrison, C M; Alexander, D M; Simpson, J; Knudsen, K K; Mullaney, J R; Rosario, D J; Scholtz, J
ABSTRACT: We present the star formation rates (SFRs) of a sample of 109 galaxies with X-ray-selected active galactic nuclei (AGNs) with moderate to high X-ray luminosities ($\mathrel {L_{\rm 2-8\, keV}}\, =\, 10^{42}-10^{45} \mathrel {\rm erg \, s^{-1}}$ ), at redshifts 1 < z < 4.7, that were selected to be faint or undetected in the Herschel bands. We combine our deep Atacama large (sub-)millimetre array (ALMA) continuum observations with deblended 8–500$\mathrel {\rm \, μ m}$ photometry from Spitzer and Herschel, and use infrared (IR) spectral energy distribution (SED) fitting and AGN – star formation decomposition methods. The addition of the ALMA photometry results in an order of magnitude more X-ray AGN in our sample with a measured SFR (now 37 %). The remaining 63 % of the sources have SFR upper limits that are typically a factor of 2–10 times lower than the pre-ALMA constraints. With the improved constraints on the IR SEDs, we can now identify a mid-IR (MIR) AGN component in 50 % of our sample, compared to only ∼1 % previously. We further explore the $F_{870\mathrel {\rm \, μ m}}$ /$F_{24\mathrel {\rm \, μ m}}$ –redshift plane as a tool for the identification of MIR-emitting AGN, for three different samples representing AGN-dominated, star formation-dominated, and composite sources. We demonstrate that the $F_{870\mathrel {\rm \, μ m}}$ /$F_{24\mathrel {\rm \, μ m}}$ –redshift plane can successfully split between AGN and star formation-dominated sources, and can be used as an AGN identification method.